Revolution, democratic transition and disillusionment;the case of romania. (Perspectives on democratic practice., 2018)
Using Romania as a case study, this book develops a fresh perspective on the transition from communism to capitalism by arguing that transition and democratisation studies should turn their attention towards processes of illusion formation and disillusionment as key to understanding the shift from one ideological framework to another.